Growth performance and carcass characteristics of finisher lambs maintained on intensive feeding or grazing with supplementation - KARIM, S A; VERMA, D L (The Indian Journal of Animal Sciences, 2014)
Orowth performance and carcass traits of finisher lambs were compared under intensive feeding (01) and grazing with supplementation (02). Initial weights were higher (P<0.05) inÂ G1 than that in G2 whereas, in the 2 groups the finishing weights were similar because the total gain in the experiment and average daily gain were higher in 02 than that in G1. The feed conversion efficiency was, however, similar in the 2 groups. Pre slaughter weight, fasted weight, empty live weight and hot carcass weights were similar in the 2 groups. Like wise the dressing yield in terms of pre slaughter weight was similar in the 2 groups while the dressing yield in terms of empty live weight was higher (P<0.05) in G1 than that in G2. Depot fat weight and per cent fat in dissected half carcass was also significantly (P<0.01) higher in G1 compared to G2. Cut proportion of leg, loin, and rack was similar in G1 and G2 while the proportion of neck and shoulder was higher in G1 and breast and fore shank was higher in G2.1t is concluded from the study that growth response of lambs was better under grazing with 300 g concentrate supplementation compared to intensive feeding while the intensively fed lambs deposited more depot.